Effect of shock wave on constant load behaviour of Pb-Free/CNT solder joint - Norliza Ismail,; Azman Jalar,; Wan Yusmawati Wan Yusoff,; Nur Shafiqa Safee,; Ariffin Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The constant load behaviour of SAC305 solder joint with addition of carbon nanotube (CNT), exposed to shock wave condition was investigated. Formulated SAC305-CNT solder pastes with 0.04 wt. % CNT were manually printed to the printed circuit board (PCB) with copper surface finish to form solder joint. The solder joint was exposed to the shock wave condition via open field blast air test using Trinitrotoluene (TNT) explosive. Nanoindentation approach was used to determine the constant load behavior of the SAC305-CNT solder joint under shock wave condition. The results showed that addition of CNT reduced the indentation depth of SAC305 solder joint at 10 mN peak load for blast test sample and control sample. Indentation depth displacement of SAC305-CNT solder joint for blast test sample and control sample were reduced about ~ 42 and ~56%, respectively, if compared to the SAC305 solder joint for blast test sample and control sample. SAC305-CNT solder joint was experienced minimal changes of stress exponent when exposed to the shock wave. The existence of CNT in the solder joint slows down the depth displacement due to constant load.